Online purchase intention among employees in DRB Hicom Defence Technologies Sdn Bhd / Ummi Farhana Hamizal - Hamizal, Ummi Farhana (Faculty of Business and Management, 2019)
The purpose of this study was to determine the online purchase intention among employees in DRB-HICOM Defence Technologies Sdn Bhd. The variables consist of price, trust, convenience and save time, website based and online purchase intention. The respondents were 97 people of employees in DRB-HICOM Defence Technologies Sdn Bhd .The finding showed that price and website based have influence on the online purchase intention among employees in DRB-HICOM Defence Technologies Sdn Bhd. These two variables showed significant relationship towards the online purchase intention among employees in DRB-HICOM Defence Technologies Sdn Bhd. The study refers to primary data and also secondary data for supporting the sampling technique. Meanwhile, the researcher use questionnaire as the method to collect all the data from sample of respondents in accomplishing the research objectives. While the data for this study was analyzed using reliability testing, descriptive, correlation and regression analysis. The result of the study presented in this research agrees that price and website based can influence customers online purchase intention. This study can be seen as a foreword to a more detailed study to be carrying by future research on the issue of the online purchase intention among employees in DRB-HICOM Defence Technologies Sdn Bhd.